Installation and Activation of a Fiber To The Home (FTTH) Network With The Addition of Optical Distribution Point (ODP) Using The Branching Method - Asril, Aprinal Adila; Yustini; Dewi , Ratna; Rifka , Silvia; Vitria , Rikky (International Journal of Advanced Science Computing and Engineering, 2023)
FTTH is a concept that uses fiber optic networks. In the FTTH optical network, one of the devices is an Optical Distribution Point (ODP). There are 2 methods for installing ODP, namely connecting the direct area cable and branching the main distribution cable or branching. In previous studies, branching was only done from ODC to ONT and Optical Light Source (OLS) as a substitute for OLT, so there is no internet network that customers can directly access using ONT. In this study, the author discusses how to activate FTTH devices from OLT to ONT customers, with a comparison before and after activation using a 1:4 passive splitter. Then the attenuation that can be produced is 28.54. Therefore network activation on ODP Branching is very efficient because the resulting attenuation does not exceed 28dB, which is in accordance with PT Telecommunications ITU-T G.948 standards.